Comparing direct and indirect forms of intergroup contact in Cyprus - Ioannou, M (2013)
This thesis examines and compares the effectiveness of direct and indirect types of contact in leading to short- or longer-term prejudice-reducing outcomes in Cyprus. Chapter 1 provides a background to the relations between Greek and Turkish Cypriots and Chapter 2 provides a theoretical introduction to the intergroup contact hypothesis (Allport, 1954) and to extended friendships (Wright, Aron, McLaughlin-Volpe, & Ropp, 1997), vicarious contact (Mazziotta, Mummendey, & Wright, 2011), and imagined contact (Crisp & Turner, 2009) which have been suggested to be alternatives and a stepping stone to direct contact when the latter is absent. Chapter 3 consists of three experiments assessing the relative effects of direct and vicarious contact (Experiments 1 and 2) and imagined contact (Experiment 3). The results show that direct, and to a weaker extent, vicarious contact lead to more positive outgroup attitudes, but that a week after contact this effect is lost. All types of contact yield less anxiety, an effect that endures in time, and direct and imagined contact yield more positive action tendencies, an effect that remains significant in time only for direct contact. Chapter 4 consists of two experiments further exploring the capacity of imagined contact to yield positive intergroup outcomes. Experiment 4 tests whether the induction of interpersonal and intergroup similarities and/or differences into a positive imagined contact scenario affects participants evaluation of the outgroup. The results show, in line with the Optimal Distinctiveness Theory (Brewer, 1971), that ‘balanced similarity’ which incorporates both similarities and differences yields more positive outgroup attitudes than the conditions focusing only on similarities or only on differences. Experiment 5 compares ‘balanced similarity’ with positive imagined contact and finds that only the former affects variables related to preparing individuals for future contact. Chapter 5 consists of a three-wave longitudinal study examining the temporal effects of direct and extended friendships on outgroup attitudes and their mediation. Both types of friendships yield a significant indirect effect on attitudes which is stronger for direct friendships and is mediated by intergroup anxiety for both types of friendships and also by ingroup norms for direct friendships. Chapter 6 presents and discusses the key findings, outlines the limitations of these studies, and suggests avenues for future research.